2016
DOI: 10.3389/fonc.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Export of microRNAs: A Bridge between Breast Carcinoma and Their Neighboring Cells

Abstract: Breast cancer is a leading type of cancer among women in India as well as worldwide. According to the WHO 2015 report, it has been anticipated that there would be a twofold rise in the death due to breast cancer among women. The heterogeneous property of breast carcinoma has been suggested to be linked with dedicated set of communication and signaling pathway with their surroundings, which culminate into progression and development of the cancer. Among the plethora of communication tools in the hand of breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…As a type of potential regulator, miRNAs serve a key role in tumorigenesis and the progression of breast cancer ( 14 ). They participate in numerous different biological processes, including cell proliferation, differentiation, invasion, migration and transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a type of potential regulator, miRNAs serve a key role in tumorigenesis and the progression of breast cancer ( 14 ). They participate in numerous different biological processes, including cell proliferation, differentiation, invasion, migration and transcription.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-based therapies have already been used as vital strategies for breast cancer treatment ( 18 ). Additionally, it has been reported that several miRNAs participated in cell tumorigenesis and metastasis ( 19 ). The overexpression of anti-oncogenic miRNAs could therefore be a novel therapeutic approach for breast cancer treatment ( 20 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small single-stranded non-coding RNAs (19–22 nucleotides in length) that play important regulatory roles, including lung carcinogenesis ( 46 50 ). Nadal et al performed microRNA profiling of adenocarcinomas subclassified by the 2015 WHO classification ( 51 ).…”
Section: Histology and Genetic Profilesmentioning
confidence: 99%
“…In a recent report, the notion that BCSCs may show a distinct miRNA expression profile compared to non‐tumorigenic breast cancer cells is widely accepted . These deregulated miRNAs may act as on comiRNAs or as tumor suppressive miRNAs towards self‐renewal, EMT, or stem cell identity maintenance of BCSC community . Besides, potential miRNAs may be involved in increased chemotherapeutic resistance of BCSCs …”
Section: Extra‐genetic Mirna Contribution In Bcscsmentioning
confidence: 99%